(untitled) (Semiárida, 2020)
This study was made in the Ea. Los Guadales-Department Caleu- Caleu, in the southeastern region of La Pampa where the landscape is mainly formed by one plateau, slopes and depressions. Three different grasslands were studied in a soft slope, along a topographical profile. In the upper site there is a perennial winter grasslands dominated by Stipa tenuis a short, native grass. Standing crop reached 215,5 gDM/m2. In the slope it grows an intermediate summer grassland dominated by Pappophorum caespitosum, a perennial warm grass. Standing crop totalized 310,5 gDM/m2. In the botton landthere is an intermediate winter grassland dominated by Stipa brachychaeta a perennial native species. Standing crop reached 469,1 gMS/m2.